Creep Feeding and Herbage Allowance on Dorper x Merino Lambs on Natural Pasture - Bianchi, Gianni; Rivero, José; Carvalho, Sérgio; Campelo, Matías; Gianelli, Marco; Pérez, Lucía (Agrociencia Uruguay, 2015)
The effect of birth type (single: S or twins: T), supplementation (0.8 % of body weight) for weaned lambs (with creep feeding: CCF or without creep feeding: SCF) and the forage allowance (low: LFA = 5 % or high: HFA = 10 % of body weight) was evaluated on the performance of 24 Australian Merino sheep (12 from single birth and 12 from twin birth), and their 36 Dorper x Australian Merino lambs. The S sheep did not show the same weight loss and body condition of their T contemporaries (0.029 or -0.007 kg/day and 2.7 or 2.5, respectively): those which were in HFA gained weight, while those in LFA lost weight (0.031 and -0.017 kg/day, respectively). Regardless of birth type, the response to supplementation of lambs was evident only in weaned lambs in LFA (0.175 and 0.132 kg/day; CCF and SCF p≤0.05, respectively).